If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3.2x=x-2
We move all terms to the left:
-3.2x-(x-2)=0
We get rid of parentheses
-3.2x-x+2=0
We add all the numbers together, and all the variables
-4.2x+2=0
We move all terms containing x to the left, all other terms to the right
-4.2x=-2
x=-2/-4.2
x=1/2.1
| -4,-3x=9 | | -6x–4=64 | | -6(n+9)=4(5-7) | | 44-6x=2 | | 3m+8=-10-6 | | 10k^2-75k+125=3 | | 10k^2-75k+125=0 | | 4n=3(n-1) | | -3(7-2x)=-1-4x | | 3+2x=4x+27 | | x+1=1,4 | | 1.66x=1.66 | | -8=2u-26 | | -4x=12=-30 | | 5-2-u=-2u-5 | | 5/y=4/10 | | 9=v/7+12 | | -8+4c=6c | | 2(2x+3)–7x=18+5(x+2x | | -4t-2=-6t+4 | | -6x=36,6 | | -19=9+4w | | -2h+2=-10+h | | 2g+6g=1 | | 3c+1=-2+6c | | -7,x+1=1 | | -x+206=39 | | 3x-(4x-6)+10x=0 | | 8z+z=8z+2 | | 3u=-8+u | | 7(x+3)-(-6x-4)=12x | | -2y=3y-8 |